2016
DOI: 10.2147/ott.s111794
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA <em>SPRY4-IT1</em> promotes malignant development of colorectal cancer by targeting epithelial&ndash;mesenchymal transition

Abstract: The clinical significance and biological functions of long noncoding RNA SPRY4 intronic transcript 1 (SPRY4-IT1) in colorectal cancer (CRC) remain largely unclear. Herein, we are the first to report that the SPRY4-IT1 was significantly upregulated in CRC tissues, serum, and cells. Higher SPRY4-IT1 expression was markedly associated with advanced Tumor Node Metastasis (TNM) stage in a cohort of 84 CRC patients. Multivariate analyses indicated that SPRY4-IT1 expression could be useful as an independent predictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…Among these four prognostic lncRNAs, SPRY4-IT1 has been widely reported in many cancer types [ 21 , 25 ], whereas none of the other three lncRNAs have been reported to be associated with human cancers. So, we attempt to further examine the expression pattern of SPRY4-IT1 in LUAD patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these four prognostic lncRNAs, SPRY4-IT1 has been widely reported in many cancer types [ 21 , 25 ], whereas none of the other three lncRNAs have been reported to be associated with human cancers. So, we attempt to further examine the expression pattern of SPRY4-IT1 in LUAD patients.…”
Section: Resultsmentioning
confidence: 99%
“…A four-lncRNA signature displayed prognostic values for LUAD. Notably, SPRY4-IT1 has been reported to be desregulated in several human cancers [ 11 , 21 , 22 ], such as hepatocellular carcinoma [ 23 ] and melanoma [ 24 ]. However, the underlying molecular mechanism of SPRY4-IT1 remains unclear in LUAD.…”
Section: Introductionmentioning
confidence: 99%
“…Among the eligible articles, 31 were from China, 3 from Japan and 1 from Czech Republic. In the including 34 studies, 29 articles analyzed the relationship between the expression of lncRNAs and gender[1620, 2429, 31, 32, 34–37, 39–46, 4851], 7 studies estimated the association between lncRNAs and tumor size[19, 24, 25, 27, 41, 42, 48], 16 studies estimated the association between lncRNAs and tumor differentiation[16, 17, 19, 24, 25, 28, 29, 34, 36, 37, 39, 40, 43, 45, 46, 48], 24 studies were about lymph node metastasis(LNM)[1620, 26, 27, 2932, 34–37, 39, 40, 42–46, 48, 50], and 20 were about distant metastasis[16, 1820, 25, 2729, 3537, 39, 40, 42–46, 48, 50], 18 studies demonstrated that lncRNAs were correlated with TNM stage[…”
Section: Resultsmentioning
confidence: 99%
“…Knockdown of lncRNA SPRY4-IT1 inhibited the migration and invasion of colorectal cancer cells and induced cell cycle arrest 19. The lncRNA FTX could inhibit HCC cell growth and metastasis both in vitro and in vivo 20.…”
Section: Discussionmentioning
confidence: 99%